Republic of Tajikistan : 2013 Article IV Consultation-Press Release and Staff Report. - International Monetary Fund. Middle East and Central Asia Dept. (Washington, D.C. : International Monetary Fund, 2021)
Tajikistan successfully completed a 3-year ECF-supported program in May 2012 and needs to continue with ambitious reforms. While growth is robust, it is non-inclusive, leading to large-scale outmigration that makes Tajikistan the most remittance-dependent country in the world. The country remains the poorest of the eight in the Caucasus and Central Asia (CCA) and stands next to last among the seven with rankings in the ease of doing business. Reliance on commodity imports, a narrow export base, and low buffers leave the economy vulnerable. Weak macroeconomic policy frameworks restrict the authorities' ability to dampen shocks. State-directed lending and investment displace market-financed activity and create fiscal risks. Presidential elections are scheduled for November.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet
Keywords: International Agreements; International Organizations; Monetary Policy; Observance; Tajikistan, Republic of